Penilaian Simpangan Pergerakan Interpolasi Angular pada Mesin Frais CNC Menggunakan Double Ballbar - Gagan Tabah; Brilliant Dwinata (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
The Computer Numerical Control machine is capable of making circular paths by moving two axes simultaneously in one of the XY, XZ, or YZ planes. If the coordination of the two axes is not good, it will cause circle interpolation errors that affect the roundness error in the machining workpiece. The error of the movement of the two axes can be measured using a double ballbar, to find out the error of the movement, it is varied with three feeding speeds. The research method used is the method of comparative analysis of double ballbar measurement results. some information from the measurement results is the error value of Circularity, Backlash, Squareness, Straightness, and Center offset. Feeding speed is very influential on geometric errors, the greater the value of feeding speed, the greater the error value. In addition to feeding speed, there are many factors that affect the results of double ballbar measurements, including ballscrew, clearance, servo mismatch, test repetition, etc.